Application of Sensor Networks to the Measurement of Subway-Induced Ground-Borne Vibration Near the Station - Hong Zhong; Di Qu; Gao Lin; Hongjun Li (International Journal of Distributed Sensor Networks)
The subway-induced ground-borne vibration poses great challenge to the environment in the nearby districts. This problem is more prominent for near-station sections of subways since more buildings and human activities are influenced. And the train would be either accelerating or decelerating in this section; the vibration induced would be different from that induced by the train running on long straight subway sections. For the purpose of evaluating human comfort and designing vibration mitigation systems in the buildings, it is necessary to measure the ground-borne vibration induced by the subway. In the presented paper, a measurement system based on the CompactRIO system and LabVIEW platform is constructed. A network of acceleration sensors is placed to collect the vibration signals. This system is used to measure the ground vibration in terms of acceleration and the corresponding Fourier spectra at a near-station section of the Shanghai Metro Line 9. Some observations have been obtained towards the ground-borne vibration induced by a train running underground near the station as well as the vibration decay with the distance from the subway tunnel.